P.003 Autoimmune Encephalitis and related disorders are not rare in British Columbia. (November 2021) - Uy, C; Chedrawe, M; Chivukula, P; Wade, J; Wong, S; Nimmo, M; Bardi, M; Carruthers, MN; Fritzler, M; Carruthers, RL
Abstract : Background: Autoimmune encephalitis (AE) is a recently described entity that presents with seizures, neuropsychiatric manifestations, and movement disorders. This observational chart review of AE aims to assess the burden of AE and related disorders at two Vancouver academic medical centers. Methods: All patients with Mitogen Laboratory AE antibody testing in 2018 were identified. Electronic hospital records were used to determine patient characteristics. Results: 1266 unique tests were ordered on 315 inpatients and outpatients. Of 37/315 (11.7%) seropositive patients, 26/37 (70.2%) patients had clinical data. Seropositive results included autoantibodies to NMDA (n=3), LG1 (n=2), CASPR2 (n=1) and paraneoplastic autoantibodies included GAD65 (n=2), PNMA2 (n=5), recoverin (n=3). There were four AE cases in 14 seronegative patients based on discharge diagnosis. 15/30 of patients had seizures and three developed status epilepticus. 15 had neuropsychiatric manifestations. 14 had a movement disorder. For inpatients, average length of stay was 24.3 days and there were 5 intensive care unit (ICU) admissions. Immunotherapies used included corticosteroids, PLEX, rituximab, IVIg, and cyclophosphamide. Conclusions: In two hospitals serving approximately two million people in 2018, there were 30 cases of AE in 2018. AE presents with a broad range of neurologic symptoms and seronegative testing does not preclude AE.